Comparative assessment of the growth performance of pangasianodon hypophthalmus in different culture strategies - Nakum Alpeshbhai Jadavbhai (KUFOS, 2013)
Abstract- Aquaculture is increasingly being focused on as the solution to food security issues the world over .Varied approaches have been employed in order to increase the production from aquaculture. A major approach has been the inclusion of alternate species in the culture basket. A key entrant group has been the pangasiids, of which the striped catfish, Pangasianodon hypophthalmus is a prime potential candidate. This species combines several desirable features like fast growth, hardiness, superior flesh quality, compatibility with other species, adaptability to culture conditions and tolerance to high stocking densities. A comparative assessment of striped catfish in different culture stratagies was carried out. The growth response was assessed with respect to the following culture situations 1) Monoculture of P hypophthalmus with fertilization 2) Monoculture with feeding 3) Monoculture with fertilization and feeding 4) Monoculture in periphyton based systems 5) Culture in combination with Indian major carps 6) Culture in combination with tilapia and common carp. The studies were conducted in outdoor cement cisterns of capacity 380 l. The duration of the study was 90 days. Feeding was done with formulated feed of overall protein content 30 % @ 10 % of the body weight once daily in treatments with feeding alone and @ 5 % in treatments with feeding and fertilization. Stocking was done @ 10 fingerlings per cistern in the case of monoculture. In the case of the combination treatments, catfish, catla, rohu and mrigal were stocked in the proportion 3:2:3:2 respectively , while in the case of culture along with tilapia and common carp the stocking ratio was 3:4:3, the overall stocking number being kept constant at 10 nos / cistern. Water quality parameters as well as fish growth were monitored at fortnightly intervals. The water quality parameters in the different treatments over the period of study were: pH 6.0 -7.3, dissolved oxygen 3.78-5.9 ppm , temperature 24.5-320C, alkalinity 68.5 – 126.9 ppm CaCo3, ammonia 0-2.5 ppm, nitrite 0-2.5ppm and nitrate 0- 5 ppm. Survival was good in all treatments with average values ranging from 85% (T5) to 93 % (T1). The % weight gain of P. hypophthalmus in different treatments ranged from 358 % in T3 to 159 % in the T5. P. hypophthalmus showed highest growth in treatment with feeding and fertilization. sThe next best growth was in the periphyton based system. In polyculture trials where two different stocking combinations were employed, the combination involving tilapia and common carp was found to be better, while catfish in combination with Indian major carps resulted in the lowest % weight gain. The inference is that viable culture options for the striped catfish are in monoculture with both feed and fertilization, followed by periphyton based approach. In the case of composite fish culture, culture along with tilapia and common carp appears to be more conducive than the combination with Indian major carps.